Pengaruh Iklan Cash Card Terhadap Minat Mahasiswa Febi UIN Sumatera Utara - Maulidah, Aula (Jurnal Etnik: Ekonomi-Teknik, 2021)
This research is motivated by increasingly rapid technologicaldevelopments, especially in the economic field, namely the paymentsystem. The card acts as a non-cash payment instrument and makesit easier for the public to make transactions or transfers betweenindividuals. This shows that people have switched from cashpayments to non-cash payments which will have an impact on thecurrent formula for money supply. Stability of money demand inpotential member states is imperative for the feasible commonmonetary policy. This study aims to determine the level of influenceof cash card advertising (atm card) on the interest of Islamiceconomics students at UIN North Sumatra and to determine whetheror not there is an effect of cash card advertising on the interests ofstudents of Febi UIN North Sumatra. The research method used is aquantitative method. Collecting data distributing respondentsIslamic economics S1 Stambuk 2019.. Research data collection usesthe questionnaire method with the Likert scale method and is givento 100 respondents. In this study, the data analysis techniques usedwere descriptive analysis and uji t using SPSS 15.0. The results ofthis study indicate that the effect of cash card advertising on theinterest of Islamic economics students at FEBI UIN North Sumatrais 15.49%. After passing several tests, it can be concluded that theeffect of cash card advertising is significant or there is a positiveinfluence on student interest